A new species of Notocotylus (Digenea: Notocotylidae) from the black-necked swan Cygnus melancorhyphus (Molina) of Argentina - Flores, Verónica Roxana; Hernández-Orts, Jesús Servando; Viozzi, Gustavo Pedro (Veterinary parasitology, regional studies and reports, 2023)
Notocotylus cygni n. sp. is described here, taken from the intestine of the black-necked swan Cygnus melancoryphus (Molina) of Patagonia, Argentina. This new species differs from other members of the genus Notocotylus by having the genital pore anterior to the caecal bifurcation (located slightly posterior to oral sucker) and the unequal number and arrangement of ventral papillae (2-3 in the lateral rows and 10-12 in the median row). Phylogenetic analyses of the 28S and ITS1-5.8S ribosomal DNA (rRNA) sequences of the new species and other notocotylid trematodes available in GenBank indicate that N. cygni n. sp. is a sister taxon of Notocotylus fosteri Kinsella et Tkach, 2005, a trematode of the intestine of the rice rat Oryzomys palustris of Florida, United States. The new species differs from N. fosteri in the unequal number and arrangement of ventral papillae, number of uterine loops, size of the egg, definitive hosts (birds vs. mammals), and disparate environment and geographical distribution (freshwater environment in Patagonia vs. salt marsh in North America). This is the eighth species of Notocotylus reported from birds in Argentina, and the ninth species from the family Notocotylidae recorded in black-necked swans in South America.
Keywords: Patagonia; Trematoda; savci; Rats; Phylogenetic relationships; kachny; Argentina; Animals; ptáci; krysa rodu Rattus; Ducks; Birds; Anseriformes; Phylogeny; Notocotylus cygni n. sp.; zvířata; fylogeneze; Mammals